Productive and morphophysiological responses of Panicum maximum Jacq. cv. BRS Zuri to timing and doses of nitrogen application and defoliation intensity - Gomide, Carlos A. M.; Paciullo, Domingos S. C.; Morenz, Mirton J. F.; Costa, Igor A.; Lanzoni, Clarissa L. (Grassland science, 2019)
The response of plants to nitrogen fertilization is subject to several factors, including the level of stress caused by defoliation. After defoliation, the plant needs to adjust its energy balance to meet the demands of shoot and root recovery. Our objective was to evaluate the production of forage mass and other morphophysiological responses of zurigrass (Panicum maximum cv. BRS Zuri) subjected to five nitrogen doses (0, 20, 40, 60 and 80 mg/dm3) that were applied at two stages (after the cut and after the appearance of the first leaf on the tiller) under two defoliation intensities (15 and 30 cm of residual height). The pot experiment was conducted in a greenhouse in a completely randomized design with three replications, and the forage mass, as well as other morphophysiological traits, was measured in three regrowth cycles after the first standardization cut. Moreover, to understand the effect of cutting height on the root system, the root mass and root carbohydrate content were evaluated at zero, seven and 14 days after the standardization cut. The root mass reduced after 7 days since cutting under the low residual height (15 cm), but no effects on the root carbohydrate content were observed. The dose of nitrogen had a marked effect on most of the variables analyzed, leading to a linear increase in the root mass, the SPAD chlorophyll content and the harvested forage mass, whereas the number of tillers increased quadratically in response to the nitrogen dose. An increase was observed in the harvested forage mass for plants under the 15 cm of residue treatment compared with those under the 30‐cm treatment (16.0 vs. 13.6 g/pot), but no effect was observed for the time of nitrogen application.